The Role of Financial Literacy and Beliefs in Investment Decision Making - Mediaty; Abdul Hamid Habbe; RIZKY INMAS PRATIWI; Angela Batara; Lidya Pratiwi Irfan; Nur Azizah (Hasanuddin Economics and Business Review, 2025)
Distinct from prior work that emphasises either financial literacy alone or broad student populations, this paper jointly examines financial literacy and financial self-efficacy as drivers of investment decision-making among accounting students a cohort of prospective finance professionals within Indonesia’s evolving OJK-led financial inclusion and investor-education ecosystem. A cross-sectional survey of 50 active undergraduate and postgraduate accounting students from Hasanuddin University and Universitas Muslim Indonesia in Makassar (tertiary education sector; accounting programmes) was analysed using PLS-SEM (SmartPLS 3.3.9, bootstrapping). Results indicate a positive, significant effect of financial literacy on investment decisions (β = 0.741, p = 0.001), while financial self-efficacy is negative and non-significant (β = −0.113, p = 0.563), with the model explaining 41.7% of variance (R² = 0.417). The evidence suggests that knowledge-based competence, rather than confidence alone, underpins higher-quality investment choices in this context. A policy-ready implication follows: curriculum-embedded financial education with supervised practice (campus investment clinics co-run with IDX–OJK partners and broker-dealers) is likely to outperform confidence-building campaigns delivered in isolation. By offering Indonesia-specific, management- and policy-relevant evidence on decision quality in an emerging-market setting, the manuscript contributes to debates at the intersection of behavioural finance, education, and economic management germane to HEBR’s readership.